Importance of the choice of heat flux parameterization in regional air–sea coupled simulations: Case studies of marine heatwaves induced by atmospheric heatwaves in 1994 and 2018 - Jeong, Taek-Bum; Bae, Hyo-Jun; Kim, Baek-Min; Yang, Sinil (Frontiers in Marine Science, 2022)
This study investigated the marine heat wave events (MHWs) that occurred near the Korean Peninsula during the summer of 1994 and 2018, using a regional air–sea coupled model. We analyzed the fifth-generation reanalysis data, ERA5, published by the European Centre for Medium-Range Weather Forecasts for both events. We found that the North Pacific High and Tibetan High were stronger than usual and were associated with warm and moist air intrusion from the subtropical regions. Air-sea interactions play an important role in the development of MHWs. Warm and moist air combined with low-level inversion and a subsequent sinking motion induced the downward latent heat flux (LHF) toward the relatively colder sea surface, resulting in increased sea surface temperatures (SSTs). To quantify the contribution of the downward LHF and evaluate the importance of the relevant physical parameters of the MHWs, we set up two coupled model experiments, namely, CPL_down and CPL_nodown. Results show that the CPL_down experiment captured the downward LHF well in both events. The model also successfully captured the observed inversion near the surface. The cold SST bias tended to be reduced as the low-level clouds decreased in the area where the downward LHF occurred. In our simulation, permitting downward LHF improved the MHW reproducibility. Therefore, we suggest that the increased downward LHF is favorable for simulating MHWs, and surface physical parameterization must be carefully performed.